Facile Synthesis of Onychines - Arita, Mao; Yokoyama, Soichi; Asahara, Haruyasu; Nishiwaki, Nagatoshi (Synthesis, 2019)
The FeCl3-mediated condensation of an α-phenylenamino ester and an enone proceeds efficiently to afford a 2-phenylnicotinate. The subsequent intramolecular Friedel–Crafts reaction yielded an onychine framework. Modifications at the 2-, 3-, and 8-positions of the onychine framework were easily achieved by altering the enamino esters and enones, which facilitated the discovery of potentially bioactive compounds.
Keywords: onychine; polysubstituted nicotinates; iron(III) chloride; intramolecular Friedel–Crafts reaction; enone